Body Mass Index, Abdominal Adiposity, Obesity, and Cardiovascular Reactions to Psychological Stress in a Large Community Sample - Douglas Carroll; Anna C. Phillips; Geoff Der (2008)
Objective: To examine the association between adiposity and the magnitude of cardiovascular reactions to acute psychological stress cross-sectionally and prospectively in a large community sample. Methods: Blood pressure and heart rate (HR) were measured at rest and in response to a brief time-pressured mental arithmetic stress in 1647 adults. At the same session and 5 years later, height, weight, waist and hip circumference were measured and body mass index (BMI) and waist-hip ratio were computed. Obesity was defined as a body mass index of ≥30kg/m2. Results: Contrary to expectations, the most robust and consistent results to emerge from cross-sectional analyses were negative associations between all three measures of adiposity and HR reactivity; those with greater BMI and waist-hip ratios and those categorized as obese displayed smaller HR reactions to stress. In prospective analyses, high HR reactivity was associated with a reduced likelihood of becoming obese in the subsequent 5 years. Conclusions: Our analyses suggest that it is low, not high, HR reactivity that is related to adiposity. Low HR reactivity, probably by reflecting generally blunted sympathetic nervous system reactions to challenge, may be a risk marker for developing obesity. SBP = systolic blood pressure; BMI = body mass index; CI = confidence interval; DBP = diastolic blood pressure; HR = heart rate; OR = odds ratio; PASAT = paced auditory serial addition test.